The use of balloon breathing stimulation media to encourage students’ participation in learning science during the Covid-19 Pandemic - Jamalulail, Qodri; Nisa, Ana Fitrotun; Prihatni, Yuli; Saputra , Bherrio Dwi (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2023)
The purpose of the article is to describe improving the effectiveness of distance learning and the creative thinking of students to understand scientific concepts, especially human respiratory system material in grade V elementary school students. The implementation step: The preparation is the creation of an innovative lesson plan. The curriculum is designed to create a distance learning experience that stays active and creative. The learning process is done online through WhatsApp Group. Based on the distance learning that has been implemented, it can be concluded by using the media "Balloon Breathing Stimulation Media" can improve students' creative thinking in science learning. Cognitive, affective, and psychomotor skills also improve as creative thinking skills increase. The use of the media " Balloon Breathing Stimulation Media " which is held by online learning can increase student motivation in the learning process. The increase in learning motivation is also a boundary with the increase in creative thinking skills in the science literacy school. Based on the analysis of the learning activities, it concluded that the use of " Balloon Breathing Stimulation Media " media in scientific learning is effective to increase the students' creative thinking ability and motivate the student in the learning process during the COVID-19.